2000
DOI: 10.1073/pnas.230429197
|View full text |Cite
|
Sign up to set email alerts
|

Functional cooperation between T helper cell determinants

Abstract: A ssociative recognition is a basic regulatory mechanism of the immune response and refers to the phenomenon in which immunity to one determinant of a multideterminant antigen enhances the response to other determinants. The cooperative effect is mediated by a determinant recognized by T helper cells (Th) and has been demonstrated for B cell responses (T-B cooperation) (1) and cytotoxic T lymphocytes responses (Th-cytotoxic T lymphocyte cooperation) (2). A similar form of associative recognition between two Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
79
0

Year Published

2001
2001
2008
2008

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 79 publications
(88 citation statements)
references
References 39 publications
9
79
0
Order By: Relevance
“…The addition of canarypox expressing CD40L had not only increased specific CD8 + T cell responses qualitatively but also improved the quality of CD8 + T cells as exhibited by more specific polyfunctional CD8 + T cells and potentially more long lived memory CD8 + T cells as determined by IL-7Rα staining. Some previous reports suggested that CD40L is also important for enhancing CD4 + T cell responses [56][57][58]. Our data are consistent with these reports in that the CD40L regimens enhanced splenocyte proliferation and Th1 cytokine production to vaccine antigens, however, only when CD40L was expressed as a membrane molecule in canarypox vector.…”
Section: Discussionsupporting
confidence: 92%
“…The addition of canarypox expressing CD40L had not only increased specific CD8 + T cell responses qualitatively but also improved the quality of CD8 + T cells as exhibited by more specific polyfunctional CD8 + T cells and potentially more long lived memory CD8 + T cells as determined by IL-7Rα staining. Some previous reports suggested that CD40L is also important for enhancing CD4 + T cell responses [56][57][58]. Our data are consistent with these reports in that the CD40L regimens enhanced splenocyte proliferation and Th1 cytokine production to vaccine antigens, however, only when CD40L was expressed as a membrane molecule in canarypox vector.…”
Section: Discussionsupporting
confidence: 92%
“…B7, ICAM-1 and CD44H). This is also consistent with the fact that the ThTh cooperation triggered by an antigen-presenting B lymphocyte is regulated by CD40 and OX-40 [26]. The up-regulation of CD40 in B lymphocytes can result either from CD40L on activated T cells or from B lymphocytes soliciting their own help from CD4 T cells [27].…”
Section: Discussionsupporting
confidence: 84%
“…Such a strategy has been successfully employed for the induction of autoantibodies against the self-proteins ubiquitin and TNF␣ using an E. coli-derived recombinant protein which had been genetically engineered to contain a known immunogenic T-helper epitope derived from a foreign antigen within its sequence. 17,18 In conclusion, we show that a genetic melanoma vaccine consisting of an immunogenic foreign helper sequence linked to a melanocytic self-antigen is able to break peripheral T cell tolerance and induce protective immunity against B16 melanoma in C57BL/6 mice. Most importantly, these results provide the scientific basis for the exploration of similar antigen-specific immunization strategies in future clinical trials for the immunotherapy of melanoma.…”
Section: Discussionmentioning
confidence: 78%